Realistic mathematics education module integrated with problem-based learning: Fostering learning interest and mathematics achievement - Nasikhun Amin; Lingga Nico Pradana; Ivayuni Listiani (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2025)
Despite growing interest in digital learning modules for mathematics instruction, few studies have examined how integrating realistic mathematics education and problem-based learning within a single e-module shapes students' learning interest and achievement, particularly in data processing. While realistic mathematics education grounds abstract concepts in contextual problems and problem-based learning strengthens engagement through authentic tasks, empirical evidence on their combined effect within a digital format remains scarce. This study examined the effect of learning interest on mathematics achievement among fifth-grade students learning through such an e-module. A quantitative correlational design was employed with 26 fifth-grade participants. Data were collected via a learning interest questionnaire and a mathematics achievement test, then analyzed using the Shapiro-Wilk test, linearity test, Pearson correlation, and simple linear regression. Results showed a positive, statistically significant effect of learning interest on achievement (p < 0.01), with learning interest explaining 27.9% of the variance, while other factors likely accounted for the remainder. These findings suggest that integrating realistic mathematics education with problem-based learning in a digital module can foster learning interest and improve mathematics achievement, offering practical implications for designing contextual, problem-oriented digital learning materials.